Ethical Dilemmas Faced by Nurses During Epidemic Crises - Nouf Enad G Alanazi, Wajid Salem Aoudh Alanazi, Fatimah Nahy Almutairi, Khulood nawaf alshammary, Eman Faraj Alshahrani, Sultanah mohammad alruaili, Hanan Abdullah Elyafaoui, Hind Dhaifallah Alotaibi (Journal of International Crisis and Risk Communication Research, 2024)
Epidemic crises, historically exemplified by events such as the Black Death, cholera outbreaks, and more recently, the HIV/AIDS epidemic, Ebola, and COVID-19, present complex ethical challenges for nurses. These crises often amplify ethical dilemmas inherent in nursing practice, demanding nuanced decision-making to balance the competing needs of individual patients, healthcare systems, and public health goals. Nurses have long been at the forefront of public health crises, acting as both caregivers and ethical decision-makers during epidemic outbreaks. This literature review explores the multifaceted dilemmas nurses face during such crises, including the conflict between duty of care and personal safety, resource allocation, patient autonomy versus public health mandates, confidentiality, and equity in care. These ethical tensions often result from systemic constraints, such as inadequate personal protective equipment (PPE) and unclear triage protocols, leading to moral distress and professional burnout. This review emphasizes the importance of institutional frameworks, professional ethical codes, and targeted training to support nurses in navigating these dilemmas. It also highlights the need for systemic reforms to ensure equitable healthcare delivery and reinforce ethical resilience among nursing professionals during epidemic crises. By synthesizing insights from historical and contemporary contexts, this review underscores the enduring relevance of ethical preparedness in enhancing the nursing response to global health emergencies.